Advances in Information Retrieval: 34th European Conference on IR Research, ECIR 2012, Barcelona, Spain, April 1-5, 2012. Proceedings - Baeza-Yates, Ricardo (Lecture notes in computer science, 2012)
This book constitutes the proeedings of the 34th European Conference on IR Research, ECIR 2012, held in Barcelona, Spain, in April 2012. The 37 full papers, 28 poster papers and 7 demonstrations presented in this volume were carefully reviewed and selected from 167 submissions. The contributions are organized in sections named: query representation; blogs and online-community search; semi-structured retrieval; evaluation; applications; retrieval models; image and video retrieval; text and content classification, categorisation, clustering; systems efficiency; industry track; and posters.
Literaturangaben
Keywords: Konferenzschrift; Social Media; Datenbanksystem; Dokumentverarbeitung; Abfrage; World Wide Web; Information Retrieval